Recurrent and superior laryngeal nerve injury in thyroid surgery: literature review - Mahyoub, Abdullatif; Aljohani, Alaa A.; Althobaiti, Abdullah J.; Alharbi, Sami S.; Alahmary, Abdulaziz A.; Algarni, Raeed S.; Alamoudi, Sultanah K.; Alshahrani, Munirah S.; Alkhaldi, Turki M.; Alqubaishi, Abdulhakim H.; Marzogi, Kaled A. (International Journal Of Community Medicine And Public Health, 2021)
Laryngeal nerve injury is considered one of the most common complications after thyroidectomy. It is associated with decreased quality of life because it will result in hoarseness of voice and aspiration. Identification of the risk factors and procedures to decrease the injury is crucial for handling laryngeal nerve injury. We searched the MEDLINE database using PubMed. Two independent reviewers reviewed the resulting papers and reviewed them based on our inclusion criteria. Based on the review results, the incidence of recurrent laryngeal nerve injury is higher than the external branch of the superior laryngeal nerve, but it is mainly due to under-reporting of the external branch of superior laryngeal nerve injury. Cancer surgery, surgeon experience, workload, re-operative procedures, and extent of surgery increased the incidence of the laryngeal nerve injury. Handling of these risk factors combined with visual dissection and inspection and/or intraoperative nerve monitoring decreased the incidence of the nerve injury. In conclusion, laryngeal nerve injury is a common post thyroidectomy complication. Anatomical dissection and visual inspection combined with intraoperative nerve monitoring is the most suitable option in high-risk thyroid surgeries.